THE ABSURDITY PORTRAYED ON JACOB LIFE IN MISS PEREGRINE’S HOME FOR PECULIAR CHILDREN BY RANSOM RIGGS - Aisyah, Imas Bening Kamal (Srawung: Journal of Social Sciences and Humanities, 2022)
This study attempts to analyze the way Jacob against his absurd life in Ransom Riggs‘Miss Peregrine’s Home for Peculiar Children. Jacob Portman experiences unexpected condition. He looks for the truth of his grandfather‘s past in order to restore his peaceful and normal life. However, after he found out about his grandfather‘s past, contrary he cannot got back to his previous life as what he planned before. His life changes into dangerous life. It made him feels hopelessness. This study aims to describe Jacob‘s absurd life, the way he against his absurd life and his characterization. To solve these problems, this study uses Absurdism theory by Albert Camus which is defined about the confrontation between human‘s desire and the world and revolt as the right way to face an absurd life and New Criticism theory as supporting theory. The result of this study shows that Jacob has five characteristics; intelligent, brave, idealistic, responsible and rebellious. His absurd life describes when his life does not go as what he planned. The feeling of hopelessness and anguish in his life are as the effects of absurd life. Moreover, the way he against his absurd life is by doing revolt. He continues and faces his life which is not as what he expects before.